Gold(III) π‐Allyl Complexes. (5th December 2019) - Rodriguez, Jessica; Szalóki, György; Sosa Carrizo, E. Daiann; Saffon‐Merceron, Nathalie; Miqueu, Karinne; Bourissou, Didier
Abstract: Gold(III) π‐complexes have been authenticated recently with alkenes, alkynes, and arenes. The key importance of Pd II π‐allyl complexes in organometallic chemistry (Tsuji–Trost reaction) prompted us to explore gold(III) π‐allyl complexes, which have remained elusive so far. The (P, C)Au III (allyl) and (methallyl) complexes 3 and 3′ were readily prepared and isolated as thermally and air‐stable solids. Spectroscopic and crystallographic analyses combined with detailed DFT calculations support tight quasi‐symmetric η 3 ‐coordination of the allyl moiety. The π‐allyl gold(III) complexes are activated towards nucleophilic additions, as substantiated with β‐diketo enolates. Abstract : Goldrausch : Die π‐Koordination von Allylgruppen zu (P, C)‐koordiniertem Gold(III) und ihre Fähigkeit, nucleophile Additionen anzutreiben, wurden authentifiziert. Spektroskopische und kristallographische Analysen in Kombination mit detaillierten DFT‐Rechnungen stützen das Bild einer gespannten, quasi‐symmetrischen η 3 ‐Koordination der Allylgruppe.